Flexible and Demountable Urban Furniture Design Approach with H-Shaped Light Concrete Modules - Kolbay, Sevda Duygu (Journal of Visual Art and Design, 2025)
Flexibility and adaptability are primary needs in the design and organization of public spaces. The main objective of this study was to model a derivative grammar in designing public furniture units with a blockwork system that can adapt to the recreational potential of any urban area. The proposed design is aimed at being shaped in line with users’ requirements as the surrounding environment is continually transforming. Hence, the potential geometric arrangements of the proposed design are meant to enable different functional scenarios. The formation and differentiation parameters of the units can be associated and interpreted according to their shape variants. In this context, the compositional principles for arrangement of the proposed H-shaped blocks are defined by a set of rules. By means of morphological, derivative, and pragmatic evaluations, different compositional options were targeted to be turned into essential grammatical schemata within the scope of this study. Design references were achieved by procedural modeling with grammar-based algorithms. Generative prototypes were created by the formulation of algorithms as the vocabulary; the syntax was developed by a shape grammar.